2018
DOI: 10.3390/w10070893
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Flood-Prone Areas in Davao Oriental, Philippines

Abstract: This study aims to quantitatively assess the impacts of climate change on the flood-prone risk areas in Davao Oriental, Philippines for the years 2030, 2050, and 2100 in comparison with the present situation by identifying flood risk zones based on multisource data, including rainfall, slope, elevation, drainage density, soil type, distance to the main channel, and population density. The future temperatures and rainfall projections from the Coupled Model Intercomparison Project Phase 5 (CMIP5) predictions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The changes will continue until every pixel undergoes the changing process. The ANN-CA model might be more reliable in terms of reduced subjectivity and uncertainty when compared to other methods such as analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) for weighting criteria [43,44]. Moreover, this study illustrates that the ANN-CA model is successfully applied to conduct multiple LULC change simulations within one CA model by considering the complicated interactions and competition among different land use categories.…”
Section: Discussionmentioning
confidence: 89%
“…The changes will continue until every pixel undergoes the changing process. The ANN-CA model might be more reliable in terms of reduced subjectivity and uncertainty when compared to other methods such as analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) for weighting criteria [43,44]. Moreover, this study illustrates that the ANN-CA model is successfully applied to conduct multiple LULC change simulations within one CA model by considering the complicated interactions and competition among different land use categories.…”
Section: Discussionmentioning
confidence: 89%
“…Climate change will aggravate the regional hydrological cycle [57]. Studies have shown that the rainfall will increase with increases in temperatures, leading to increased flood intensity [58]. Due to the well-developed water system in the lower reaches of the Huai River Basin, there is little difference in river network density among different regions.…”
Section: Index System Of Flood Drainage Rights Allocationmentioning
confidence: 99%
“…However, the AHP method shows some limitations due to the subjectivity in choosing the value of the indicator weighting from the arbitrary judgments of experts [1,6,13]. The CR is the crucial element when generating HI for the multi-criteria analysis using AHP method.…”
Section: Effects Of Varying Consistency Ration (Cr) On Flood Hazard Mapmentioning
confidence: 99%
“…AHP is a popular and widely used method developed by Saaty [34] to solve a wide range of multi-criteria decision-making problems, combined with the use of a pairwise comparison matrix that calculates the weights of every criterion considered. Recently, researchers have given considerable attention to using AHP in flood risk assessment [1,4,13,35,36]. In those case studies, it has been shown that AHP can assess and map flood risk areas with reliable accuracy.…”
Section: Introductionmentioning
confidence: 99%